2010
DOI: 10.1002/pbc.22611
|View full text |Cite
|
Sign up to set email alerts
|

Complete response to carboplatin, gemcitabine, and paclitaxel in a patient with advanced metastatic renal medullary carcinoma

Abstract: Renal medullary carcinoma (RMC) is a rare and aggressive malignancy seen primarily in patients with sickle-cell trait. We report a complete response to carboplatin, paclitaxel, and gemcitabine in a patient with advanced metastatic RMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…The most significant clinical challenge presented by RMC is that chemo-, immuno-and radiotherapy have all been unsuccessful for the treatment of RMC, based on previous studies (4,5,(17)(18)(19)(20)(21)(22). Therefore, an early diagnosis may improve the survival rates of patients with RMC.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant clinical challenge presented by RMC is that chemo-, immuno-and radiotherapy have all been unsuccessful for the treatment of RMC, based on previous studies (4,5,(17)(18)(19)(20)(21)(22). Therefore, an early diagnosis may improve the survival rates of patients with RMC.…”
Section: Discussionmentioning
confidence: 99%
“…First-line treatment may include cytotoxic chemotherapy with palliative intent, as most patients still die within 1 year of diagnosis. 1 Walsh et al 6 reported an 11-year-old African American male patient with sickle cell trait, with advanced metastatic renal medullary carcinoma that was treated with a paclitaxel, gemcitabine, and carboplatin regimen. There was an initial appropriate response to systemic therapy; however, he ultimately had disease progression with leptomeningeal involvement, and he died 24 months after initial diagnosis.…”
Section: Further Diagnostic Assessment and Managementmentioning
confidence: 98%
“…Partial responses were obtained on a short period using the MVAC regimen (methotrexate, vinblastine, doxorubicin, and cisplatin) [7]. Responses have also been reported using cisplatin or carboplatin in combination with gemcitabine and paclitaxel, however, death occurred 10, 12 and 24 months after the diagnosis [8]. Only two studies reported on patients in continuous remission [5,9].…”
Section: Discussionmentioning
confidence: 99%